Evaluación de las características organolépticas y nutricionales de un embutido (salchicha tipo Frankfurt) a partir del filete de vieja azul (Andinoacara rivulatus) considerada especie nativa de Ecuador - Valle Vera, Shirley Paulette (2022)
The purpose was to investigate the organoleptic and nutritional characteristics of a sausage made from the fillet of the native fish Vieja azul (Andinoacara rivulatus), we proceeded to use a multifactorial design AxBxC, with 8 treatments, 3 replications with a total of 24 experimental units to determine the effects between treatments we used the Tukey test with a 95% confidence level (p< 0. 05), the effect of the different levels and treatments was determined, the results of the data obtained were analyzed using the statistical packages "Statgraphics",